Phytochemical Screening and Medicinal Importance of Caylusea Abyssinica Root Bark Extracts - Willy Kemboi; Marianne Wanjiru Mureithi; Kefa Ogonyo Bosire (Adventist University of Africa, 2023)
Background: Herbal plants contain important substances termed phytochemicals. Phytochemicals occur naturally in herbal plants as secondary metabolites with vital properties, such as antibiotics. Recently, there has been a keen focus on herbal plants such as Caylusea abyssinica because of their ability to cure diseases and conditions that are challenging to modern medicine; hence, they are relevant to human health today. This study was conducted to screen the phytochemicals of Caylusea abyssinica and explain their medical significance. Methods: GC-MS and LC-MS were used to determine the phytochemicals extracted from the root bark of Caylusea abyssinica. Root bark samples were extracted using hexane solvent and analyzed using chromatographic methods. Results: Using GC-MS/LC-MS and solvent extraction, 16 new phytochemicals were identified. The phytochemicals are Methyl benzoate, imine, benzaldehyde, O-methyloxime, o-xylene-α,α'-dithiol, benzene, (ethenylsulfinyl), ethanone, 1-phenyl-oxime, benzene-ethanamine, N-(1-methyl ethylidene), aziridine, 2,3-dimethyl-1- (phenylmethyl)-, trans, benzyl 2-pyrrolidinecarboxylate, diphenyl(2-pyrrolidinyl) methanol, pyrrolidine-2-carboxylic acid, methylphenylamide, 2-isothyl ocyanatoethyl, N,N'-diphenethylthiourea, methyl-2-isothiocyanato-3-phenylpropionate, ethylbenzene, 4-benzyloxy-phenylacetonitrile and 1,3,5-cycloheptatriene, 7-ethyl. This study demonstrates the medical importance of phytochemicals. Conclusion: Cyalusea abyssinica is an essential herb that is rich in various medically important phytochemicals.